Science and the media alternative routes in scientific communication - Bucchi, Massimiano (Routledge studies in science, technology and society, 1998)
"In the days of global warming and BSE, science is increasingly a public issue. But what should scientists communicate to the general public? To what extent can the public understand and be involved in scientific debate? How does this involvement affect the shaping and organization of scientific activity? Why do scientists sometimes turn to the media and publicize their findings rather than communicating their findings only with their peers?"--BOOK JACKET. "Science and the Media provides a theoretical framework which conclusively answers all these questions and allows us to understand why and how scientists address the general public."--BOOK JACKET.